Pharmacovigilance Programme of India: A Review (Global Journal of Medical Research, 2020)
In India, a proper adverse drug reaction monitoring system was started in 1986 with 12 regional centers. In 1997, India became the member of the World health organization Programme for International Drug watching managed by the Upsala Monitoring Centre, Sweden. At origination, 6 regional centers were created in Mumbai, New Delhi, Kolkata, Lucknow, Pondicherry, and Chandigarh for ADR watching within the country. Promoting safe use of drugs may be a priority of the Indian Pharmacopoeia Commission that functions as the National Coordination Centre for Pharmacovigilance Programme of India. Today, 179 adverse drug reactions monitoring centers presently report adverse events to the National coordinative centre in India.
Keywords: vigiflow; UMC; death; thalidomide; reporting form; phocomelia